ANALISIS KANDUNGAN LOGAM BERAT ABU BATUBARA PLTU BANGKO BARAT KAB. MUARA ENIM SUMATERA SELATAN - Firman Firman (Fakultas Teknik Universitas Khairun, 2020)
Coal combustion product (CCP) from Bangko Barat Power Plant is used as landfill material in acidic overburden layers. CCP is categorized as hazardous and toxic waste (PP No.101/2014) from specific sources and is known to contain heavy metals. This study aims to analyze the heavy metal content of coal combustion product from Bangko Barat Power Plant, Muara Enim Regency, South Sumatra Province. Heavy metal content of CCP includes Hg, Cd, Cu, Ag, Ni, Pb, As, Cr, Sn, Zn dan Mn. Heavy metal content analysis to ensure overburden piling by utilizing CCP, either with a long-term safe coating or mixing scheme. The analysis was carried out by using ICP-MS test, XRF test, XRD test, analysis of grain size and grain morphology. Samples of fly ash and bottom ash were categorized as non- hazardous and toxic waste based on the results of the ICP-MS test compared to the values of TK-A, TK-B and TK-C. Heavy metal content that needs attention from coal ash is As (4.4-20 ppm), Cr (26-43 ppm), Cu (30.7-42.6 ppm), Pb (22,2-29,3 ppm), Zn (77.5-128 ppm), Ni (10,6-24,8 ppm) and Mn (144-396 ppm). The content of other heavy metals is relatively low (Hg, Cd, Ag and Sn) and the threshold is not exceeded. Monitoring the quality of runoff water from landfill area using CCP to be controlled so that the heavy metal content does not endanger the health of living things.